2014
DOI: 10.1007/s10597-014-9758-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health in Adults with Serious Mental Illness: Needs for and Perspectives on Care

Abstract: This study used qualitative methods to investigate barriers to and facilitators of oral health care among 25 adult community mental health outpatients with serious mental illness (SMI). Participants completed 30- to 60-min, semi-structured interviews that were recorded and transcribed. Qualitative analysis was used to characterize common themes. Results showed that lack of awareness of dental problems, poverty, and dental care access were key barriers to oral health care. When oral health care was accessed, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 26 publications
0
58
0
Order By: Relevance
“…This includes a reluctance to talk to patients about the relationship between mental health and oral health (Berry & Davidson ; McKibbin et al . ). Few dentists appear adequately prepared in providing care to patients living with mental illness (Friedlander & Marder ; Griffiths et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This includes a reluctance to talk to patients about the relationship between mental health and oral health (Berry & Davidson ; McKibbin et al . ). Few dentists appear adequately prepared in providing care to patients living with mental illness (Friedlander & Marder ; Griffiths et al .…”
Section: Discussionmentioning
confidence: 97%
“…; McKibbin et al . ). This study explored the issue of oral health with mental health professionals including nurses working in the Perth metropolitan area, Western Australia and the different ways in which access to care, knowledge and preventative regimens might be enhanced for adults with mental health disorders.…”
Section: Introductionmentioning
confidence: 97%
“…In the present study, both patients and caregivers stated that patients paid little attention to their oral and dental health. In a qualitative study from the United States that included 25 individuals with severe mental illness, it was found that patients' ignorance, lack of recognition of dental problems, and financial limitations were the most important barriers to oral and dental health . Psychiatric nurses can create standard checklists to identify patients' oral and dental health problems, and can collaborate with caregivers to support patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study from the United States that included 25 individuals with severe mental illness, it was found that patients' ignorance, lack of recognition of dental problems, and financial limitations were the most important barriers to oral and dental health. 23 Caregivers play an important role in preserving and maintaining the physical health of individuals with severe mental illness. 25 In the present study, caregivers wanted to support their patients in maintaining and improving their physical healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Oral health literacy was limited with the absence of pain the primary concern (McKibbin et al . ), and interacting social, practical and affective barriers, including shame, hindered access to dental services (Persson et al . , Ford et al .…”
Section: Discussionmentioning
confidence: 99%